Maternal care affects the phenotype of a rat model for schizophrenia - van Vugt, Ruben W. M.; Meyer, Francisca; van Hulten, Josephus A.; Vernooij, Jeroen; Cools, Alexander R.; Verheij, Michel M. M.; Martens, Gerard J. M. (Frontiers in Behavioral Neuroscience, 2014)
Schizophrenia is a complex mental disorder caused by an interplay between genetic and environmental factors, including early postnatal stressors. To explore this issue, we use two rat lines, apomorphine-susceptible (APO-SUS) rats that display schizophrenia-relevant features and their phenotypic counterpart, apomorphine-unsusceptible (APO-UNSUS) rats. These rat lines differ not only in their gnawing response to apomorphine, but also in their behavioral response to novelty (APO-SUS: high, APO-UNSUS: low). In this study, we examined the effects of early postnatal cross-fostering on maternal care and on the phenotypes of the cross-fostered APO-SUS and APO-UNSUS animals later in life. Cross-fostered APO-UNSUS animals showed decreased body weights as pups and decreased novelty-induced locomotor activity as adults (i.e., more extreme behavior), in accordance with the less appropriate maternal care provided by APO-SUS versus their own APO-UNSUS mothers (i.e., the APO-SUS mother displayed less non-arched-back nursing and more self-grooming, and was more away from its nest). In contrast, cross-fostered APO-SUS animals showed increased body weights as pups and reduced apomorphine-induced gnawing later in life (i.e., normalisation of their extreme behavior), in line with the more appropriate maternal care provided by APO-UNSUS relative to their own APO-SUS mothers (i.e., the APO-UNSUS mother displayed more non-arched-back nursing and similar self-grooming, and was not more away). Furthermore, we found that, in addition to arched-back nursing, non-arched-back nursing was an important feature of maternal care, and that cross-fostering APO-SUS mothers, but not cross-fostering APO-UNSUS mothers, displayed increased apomorphine-induced gnawing. Thus, cross-fostering not only causes early postnatal stress shaping the phenotypes of the cross-fostered animals later in life, but also affects the phenotypes of the cross-fostering mothers.